The Implementation of Religious Moderation Values in the Teaching of Islamic Religious Education at MIN 7 Ngawi - Rofiah, Binti Khoirur; Haris, Abdul; Yazid, Syamsurizal (Indonesian Journal of Advanced Research, 2025)
This research aims to describe the objectives, describe the implementation of religious moderation values ​​in PAI learning at MIN 7 Ngawi. This research uses a qualitative case study type approach. Data collection techniques include observation, in-depth interviews with research subjects (Head of the Foundation, Principal of MIN 7 Ngawi School and PAI subject teachers), and documentation. The data collected was validated using triangulation of techniques and sources. The data obtained was then analyzed using three techniques, namely pattern matching, explanation creation and time series analysis. The research results show that MIN 7 Ngawi implements the values ​​of religious moderation because Religious Education is a Pillar of Religious Moderation, the Madrasah Environment is a Place for Education of Moderate Values, PAI is an Instrument of Holistic Education and there is a Government Policy Supporting Religious Moderation. MIN 7 Ngawi implements Bergama's moderation values ​​through three stages, the first is planning, the second is implementation and the last is evaluation.